Characterising a handheld quantum key distribution system with emulated beam steering - Lowndes, D; Schreier, A; O'Brien, DC; Rarity, JG (SPIE, 2021)
We present a miniaturised free-space quantum key distribution (QKD) system which allows key exchange between a handheld transmitter and a fixed terminal. The QKD system requires to be optically aligned emphasising the need of a beamsteering unit for later applications. To maintain within the size, weight and power restrictions, the active beamsteering hardware is exclusively located inside the receiver. Our target is consumer use so we present rigorous characterisation against a range of background light levels to show anticipated performance outside of a laboratory environment. Experimental results show a reduction in the raw count rate commensurate with the transmission of the added components (74.5%) and a small degradation of the error rate (0.5 percentage points) due to the worse signal-to-noise ratio. These combine to a 50% reduction in estimated secret key rate of the system with the additional components for beam steering.